2014
DOI: 10.1155/2014/691946
|View full text |Cite
|
Sign up to set email alerts
|

A Comparison of Antegrade Percutaneous and Laparoscopic Approaches in the Treatment of Proximal Ureteral Stones

Abstract: Purpose. To compare the effectiveness and safety of retroperitoneal laparoscopic ureterolithotomy (RLU) and percutaneous antegrade ureteroscopy (PAU) in which we use semirigid ureteroscopy in the treatment of proximal ureteral stones. Methods. Fifty-eight patients with large, impacted stones who had a history of failed shock wave lithotripsy (SWL) and, retrograde ureterorenoscopy (URS) were included in the study between April 2007 and April 2014. Thirty-seven PAU and twenty-one RLU procedures were applied. Sto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
24
1
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(31 citation statements)
references
References 24 publications
0
24
1
1
Order By: Relevance
“…PNL is another treatment option in the treatment of large ureteral stones that cannot not be reached retrogradely and located in the ureteropelvic junction [13]. Furthermore, pushing the stone back to the renal pelvis and performing a percutaneous approach can be an alternative technique to L-RU and F-URS.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…PNL is another treatment option in the treatment of large ureteral stones that cannot not be reached retrogradely and located in the ureteropelvic junction [13]. Furthermore, pushing the stone back to the renal pelvis and performing a percutaneous approach can be an alternative technique to L-RU and F-URS.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, pushing the stone back to the renal pelvis and performing a percutaneous approach can be an alternative technique to L-RU and F-URS. Studies in the literature reported high success rates as 86-100% with PNL using these techniques [13,14,15]. In a recent study, Long et al evaluated the efficacy and safety of mini-PNL in the treatment of large proximal ureteral stones [16].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…131 For large (>15 mm), impacted proximal ureteral stones, the stone-free rate with antegrade URS ranges between 98.5% and 100% with a low risk for complications. 130,[132][133][134][135][136] Laparoscopic, robotic or open ureterolithotomy may be considered when ureteroscopic and percutaneous procedures have failed or concomitant surgery is required. …”
Section: Antegrade Urs and Ureterolithotomymentioning
confidence: 99%
“…Ureteral avulsion and strictures are rare (< 1%). Previous perforations are the most important risk factor for complications.3.4.3.1.4.2 Percutaneous antegrade ureteroscopy Percutaneous antegrade removal of ureteral stones is a consideration in selected cases, i. e. large, impacted proximal ureteral calculi with dilated renal collecting system[284], or when the ureter is not amenable to retrograde manipulation[259,[285][286][287][288]. Percutaneous antegrade removal of ureteral stones is an alternative when SWL is not indicated or has failed, and when the upper urinary tract is not amenable to retrograde URS.…”
mentioning
confidence: 99%